Edukacyjne aspekty interwencji policyjnych = Educational aspects of police interventions - Stankiewicz, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The course of intervention varies depending on the nature of the event. Providing information - educating people involved in an intervention, may dominate the course of policing. Providing adequate knowledge on, for example, rights and obligations should be fully implemented in local communities where a police officer - a district police officer - is obliged to go beyond his/her tasks in order to fulfill his/her tasks as fully as possible. The article indicates the educational aspects accompanying the conducted police interventions. These contents were developed on the basis of a substantive analysis of the texts and source materials.
Keywords: edukacja; społeczeństwo; interwencja policyjna; education; society; police intervention